Managing Refractoriness: Modern Strategy for Refractory Celiac Disease - Grzeszczak, Roksana; Fałczyńska, Aleksandra; Balak, Aleksandra; Szkudlarek, Weronika; Rotte, Katarzyna; Grabarczyk, Maksymilian; Piotrowski, Igor (Quality in Sport, 2026)
Celiac disease (CD), also known as gluten-sensitive enteropathy, is the most common autoimmune disorder in today’s society. CD is associated with both human leukocyte antigen (HLA) and non-HLA genes. It often coexists with other autoimmune diseases, such as juvenile diabetes and thyroid disease. Diagnosis often relies on biopsy results, but serological tests are also very useful when screening patients suspected of having CD. Although our knowledge of celiac disease seems thorough, the pathogenesis of refractory celiac disease (RCD) is still under research. Treating RCD can be challenging, and it is crucial to provide care in experienced tertiary centers. Treatment may involve dietary and pharmacological approaches, depending on the type of RCD. This reduces the risk of disease progression and alleviates the symptoms. Investigations into other innovative treatment methods are ongoing.